The Culture of Memory: The Approach of Reyes Mate - Gan-Krzywoszyńska, Katarzyna; Leśniewski, Piotr (ETHICS IN PROGRESS, 2014)
The aim of the article is to present Reyes Mate’s project for a culture of memory. Western culture/tradition tends to erase and blur the traces of crimes (even genocides) in order to achieve/restore peace; however, at the same time, this leads to ignoring the victim’s suffering and, in consequence, helps the wrongdoer. Following Reyes Mate, we argue that a memory of past injustices must constitute an integral part of the present and is the only means to prevent the hermeneutic death of victims. Any project for justice must put victims at the center of reflection. Memory is the beginning of the process that leads to reconciliation, for it makes it possible to redress both the victim and society. Moreover, it enables us to reclaim both the victim and wrongdoer as members of society. A culture of memory would also be a response to the failure of knowledge. Cases of extreme violence elude and transcend cognition; they are not only unthought but also unthinkable. Therefore, memory is a consequence not of discovering but of revealing the past: it follows from the fact that unthought exists and the unthinkable happened, which proves that our knowledge is limited and that we are able [and eager] to “invisibilize” victims’ suffering and depriving injustices of meaning. This is why memory should be the starting point for reflection on a new philosophical program against lassitude and oblivion, as well as on idealistic/anti-realistic and Enlightenment ideas. Memory reveals hidden aspects/dimensions of our reality and becomes at the same time an epistemic imperative and fundamental philosophical category.